Top Management Team Characteristics and Corporate Social Responsibility in China: Moderating Effect of Compensation - SONG, DANYANG (2020)
This study explores the relationship between top management team (TMT) characteristics and corporate social responsibility (CSR) under the moderating effect of executive compensation for 563 companies listed in China for the period 2014 to 2018. While it is proved by many researchers that TMT characteristics influence CSR, the inconsistent effect of specific characteristics observed in previous research implies the possible impact of other contingent variables. Through incorporating agency theory and upper-echelons theory, this study further investigates the moderating role of executive compensation, a significant component of corporate governance. The results show that TMTs’ average age, education level, overseas experience and academic experience are positively related to the CSR performance, while the average tenure influences the CSR performance negatively. Moreover, it is found that the compensation moderates the influence of some characteristics on CSR significantly. However, the direction and intensity of the moderating effects vary from different incentive compensation and individual characteristics. More specifically, monetary compensation strengthens the positive influence of executives’ age, education level, academic experience significantly, whereas the equity incentive weakens the positive relationship between overseas experience and academic experience. The results indicate that matched TMT characteristics and compensation design would help TMT characteristics exert a greater influence on CSR performance. Therefore, TMT composition and executive compensation should be considered at the same time to prompt CSR in China more effectively.